The impact of different corneal refractive surgeries on binocular dynamic visual acuity - Wang, Yuexin; Guo, Yining; Li, Yuanting; Zhang, Yu; Yuan, Yifei; Wu, Tingyi; Chen, Yueguo; Li, Xuemin (Frontiers in Neuroscience, 2023)
Purpose To investigate the influence of different corneal refractive surgeries on dynamic visual acuity (DVA), and explore its potential influence factors. Methods This was a prospective non-randomized study. Adult myopic patients undergoing bilateral laser-assisted sub-epithelial keratomileusis (LASEK), femtosecond laser-assisted in situ keratomileusis (FS-LASIK), or small incision lenticule extraction (SMILE) with Plano refraction target were enrolled. Uncorrected and corrected distance visual acuity (UDVA/CDVA), manifest refraction and binocular optotype-moving DVA of 40 and 80 degrees per second (dps) were evaluated pre-operatively and post-operatively up to 3 months. Results The study included 264 eyes of 132 subjects, with an average age of 27.0 ± 6.7 years, and females accounted for 59% of the participants. Significant improvement was observed at the 3-month visit for 40 dps (SMILE, P = 0.001; LASEK, P = 0.006; FS-LASIK, P = 0.010) and 80 dps (SMILE, P = 0.011; LASEK, P = 0.025; FS-LASIK, P = 0.012) DVA. Adjusting for pre-operative DVA, there was no significant difference in DVA among groups at 3 months post-operatively (P > 0.05 for multiple comparisons). Overall, multiple linear models demonstrated that post-operative DVA at 3 months was correlated with pre-operative DVA (40 dps, β = 0.349, P = 0.001; 80 dps, β = 0.447, P < 0.001), pre-operative spherical equivalent (40 dps, β = 0.311, P = 0.003; 80 dps, β = 0.261, P = 0.009) and post-operative UDVA (40 dps, β = −0.224, P = 0.024; 80 dps, β = −0.188, P = 0.05). Conclusion Dynamic visual acuity at 3 months post-operatively of the three corneal refractive surgeries was better than that before the surgery in adult myopic patients, and there was no significant difference among different surgical techniques. Post-operative DVA at 3 months was found correlated with pre-operative DVA, pre-operative SE, and post-operative UDVA. With further improvement, DVA could be a promising functional visual indicator for myopic patients undergoing refractive surgeries.